Pengaruh Kompensasi Dan Gaya Kepemimpinan Transformasional Terhadap Produktivitas Kerja Karyawan Industri Rumah Congo Sedayu, Bantul-Yogyakarta - Suhartinah Suhartinah (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
Abstrak Research purposes of this is to describe (1) the effect of compensation on employee productivity, (2) the influence of transformational leadership style on employee work productivity, (3) influence of compensation and transformational leadership style to employee work productivity. this study using the variables of compensation, leadership style transformation and employee productivity. Its population is employees of industy congo Sedayu, Bantu-Yogyakarta employees numbering 30 people. The sample used is a sampel census or sampel so that the total population is used as a sample. Methods of data collection using questionnaires, while for the analysis technique using multiple regression analysis supported by F test, T test, and coefficient of determination. In this study, the results showed that (1) the compensation had a positive and significant effect on the work productivity of the employees of congo Sedayu, Bantul-Yogyakarta α = 0,05 (p = 0,018), (2) transformational leadership style had positive and significant effect on productivity ????=0,05 (p=0,023), compensation and transformation leadership style have positive and signifanct effecton work produktivity of congo sedayu, Bantul-Yogyakarta ????=0,05 (p=0,000). Keywords: compensation, transformational leadership and work productivity